Postoperative Ankle Imaging, 2022 - Shrestha, Roman; Sill, Andrew P.; Haug, Logan P.; Patel, Karan A.; Kile, Todd A.; Fox, Michael G. (Seminars in Musculoskeletal Radiology, 2022)
Postoperative ankle imaging requires knowledge of the underlying surgical techniques, the usefulness of various imaging modalities, as well as an appreciation for the desired clinical outcomes. Surgical procedures discussed in this article are tibiotalar fracture fixation, tibiotalar, subtalar, and tibiotalocalcaneal arthrodesis, total ankle arthroplasty, talar osteochondral lesion repair and grafting, lateral ligamentous repair and reconstruction, and peroneal and Achilles tendon repair and reconstruction. Imaging can play a vital role in determining if the expected outcome has been achieved and identifying complications, with particular emphasis placed on the use of radiographs, computed tomography (including weight-bearing), magnetic resonance imaging, and ultrasonography.
Keywords: ankle; arthrodesis and arthroplasty; osteochondral lesion; magnetic resonance imaging and computed tomography; tendon and ligament repair